2021
DOI: 10.3991/ijim.v15i19.22137
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Usage of Mobile Technologies Among the Hearing-Impaired Students in Learning English as a Second Language (ESL)

Abstract: <p>With the emergence of mobile technologies in education, the special needs students are gaining the infinite benefits that could enhance their learning sessions. Numerous studies are conducted on the usage of mobile technologies    among the special needs students including their acceptance towards the technologies, its advantages as well as the obstacles on the utilisation of mobile technologies. However, fewer studies are done on the usage of mobile technologies among the hearing-impaired (HI) studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In correspondence with the finding of Nasir et al (2021), the current study found that mobile is a very effective tool for the socialization of SWHI.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In correspondence with the finding of Nasir et al (2021), the current study found that mobile is a very effective tool for the socialization of SWHI.…”
Section: Discussionsupporting
confidence: 84%
“…For many people, English is a second language but for hearing-impaired individuals, it can be a third language so it can become challenging for them to get a command of the English language. Nasir et al (2021) conducted a study to explore the usage of mobile technology among hearing-impaired adolescents in learning English as a second language. It was found that adolescents with hearing impairment use mobile technology to learn the English language through various platforms such as social media, Google Translate online dictionary, emails, and video chatting with their English teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Nasir (2021) students with hearing impairment use social media to develop their English language skills. Perhaps, the findings of the present study have revealed that students with hearing impairment use social media more for social relationships and entertainment (Huang, et.al., 2021) rather than academic accomplishments.…”
Section: Discussionmentioning
confidence: 99%
“…application. In this regard, Nur Ain Mat Nasir et al (2021) discuss the use of mobile technology, such as Kahoot! among pupils with hearing impairment (HI) in the English language learning session.…”
Section: Kahoot! Applicationmentioning
confidence: 99%